2020
DOI: 10.1016/j.celrep.2020.01.099
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferons Suppress Anti-parasitic Immunity and Can Be Targeted to Improve Treatment of Visceral Leishmaniasis

Abstract: Graphical Abstract Highlights d Type I IFNs are major upstream regulators of CD4 + T cells from VL patients d Type I IFN signaling-deficient mice have improved control of Leishmania donovani d Type I IFNs inhibit IFNg but promote IL-10-producing antigen-specific CD4 + T cells d Blocking type I IFN signaling enhances anti-parasitic CD4 + T cell responses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 94 publications
2
42
0
Order By: Relevance
“…The role of IL-10 in negative regulation of Th1 responses has been highlighted by lethal outcomes of IL-10 knockout or neutralization in toxoplasma or trypanosome mouse infection models [ 37 ]. Many immunoregulatory molecules and pathways, most notably those associated with interleukin-10 (IL-10) production, are activated following infection, which can suppress antiparasitic CD4 + T cell functions [ 38 ]. Recent findings have suggested that IL-10 impairs the Th1 protective response and allows the parasites to survive in hydatid patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of IL-10 in negative regulation of Th1 responses has been highlighted by lethal outcomes of IL-10 knockout or neutralization in toxoplasma or trypanosome mouse infection models [ 37 ]. Many immunoregulatory molecules and pathways, most notably those associated with interleukin-10 (IL-10) production, are activated following infection, which can suppress antiparasitic CD4 + T cell functions [ 38 ]. Recent findings have suggested that IL-10 impairs the Th1 protective response and allows the parasites to survive in hydatid patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, whole lung transcriptomic analyses have confirmed that the induction of IFN‐I response genes occurs in a broad range of lung diseases including viral infection as well as in HDM‐dependent allergic airway inflammation 87 . Reports that IFN‐I can suppress IFNγ responses 88 and regulate the balance of T‐follicular versus T‐effector CD4 + T‐cell differentiation 89 may offer potential mechanisms for the enhancement of Th2 responses by IFN‐I.…”
Section: How Do Conventional Dcs Drive the Development Of Th2 Cells?mentioning
confidence: 98%
“…86 Recently, whole lung transcriptomic analyses have confirmed that the induction of IFN-I response genes occurs in a broad range of lung diseases including viral infection as well as in HDM-dependent allergic airway inflammation. 87 Reports that IFN-I can suppress IFNc responses 88 and regulate the balance of T-follicular versus T-effector CD4 + T-cell differentiation 89 may offer potential mechanisms for the enhancement of Th2 responses by IFN-I. IL-33 is an alarmin belonging to the IL-1 superfamily that binds a heterodimeric receptor comprising ST2 (IL1RL1) and IL-1 receptor accessory protein (IL1RAP) and activates NF-jB and MAP kinase pathways (Figure 1).…”
Section: The Need For Epithelial and Stromal Factors: Tslp Il-33 Ilmentioning
confidence: 99%
“…As an interferon-induced protein, IFI44 expression levels directly re ect IFN-α/β activity. IFN-α/β plays an important role in defending against infection from many parasites such as Leishmania donovani [28], Plasmodium [29], Toxoplasma [30], and Trypanosome brucei [31]. Therefore, it is speculated that IFI44 might have indirect anti-protozoan functions.…”
Section: Immune-related Proteinsmentioning
confidence: 99%